2007
DOI: 10.1029/2006wr004932
|View full text |Cite
|
Sign up to set email alerts
|

A field assessment of the value of steady shape hydraulic tomography for characterization of aquifer heterogeneities

Abstract: [1] Hydraulic tomography is a promising approach for obtaining information on variations in hydraulic conductivity on the scale of relevance for contaminant transport investigations. This approach involves performing a series of pumping tests in a format similar to tomography. We present a field-scale assessment of hydraulic tomography in a porous aquifer, with an emphasis on the steady shape analysis methodology. The hydraulic conductivity (K) estimates from steady shape and transient analyses of the tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
131
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 43 publications
1
131
0
2
Order By: Relevance
“…During the last decade, HT has been intensively studied both numerically and experimentally to assess its performance with a few field applications (Straface et al, 2007;Bohling et al, 2007). HT studies have covered several flow conditions, ranging from steady-state flow (Yeh and Liu, 2000) to transient flow in both confined and unconfined aquifers (Cardiff and Barrash, 2011).…”
Section: A H Alzraiee Et Al: Hydraulic Tomography Data Fusionmentioning
confidence: 99%
“…During the last decade, HT has been intensively studied both numerically and experimentally to assess its performance with a few field applications (Straface et al, 2007;Bohling et al, 2007). HT studies have covered several flow conditions, ranging from steady-state flow (Yeh and Liu, 2000) to transient flow in both confined and unconfined aquifers (Cardiff and Barrash, 2011).…”
Section: A H Alzraiee Et Al: Hydraulic Tomography Data Fusionmentioning
confidence: 99%
“…A broad-scale non-invasive survey technique to investigate the subsurface would potentially allow rapid and broad spatial scale estimation at potentially fine spatial resolutions of vadose zone heterogeneity, compared to other point scale techniques which provide only local estimates of hydraulic properties (Bohling et al, 2007). The point-scale techniques can be used to ground-truth the broad-scale survey.…”
Section: Introductionmentioning
confidence: 99%
“…They include numerical studies [e.g., Gottlieb and Dietrich, 1995;Yeh and Liu, 2000;Bohling et al, 2002;Yeh, 2005, 2006;Fienen et al, 2008;Ni and Yeh, 2008;Castagna and Bellin, 2009;Xiang et al, 2009;Liu and Kitanidis, 2011], followed by laboratory sandbox studies [e.g., Liu et al, 2002;Brauchler et al, 2003;Illman et al, 2007;Liu et al, 2007;Illman et al, 2008;Yin and Illman, 2009;Illman et al, 2010;Berg and Illman, 2011a;Illman et al, 2012] and then experimental field studies [e.g. Bohling et al, 2007;Li et al, 2007;Straface et al, 2007;Cardiff et al, 2009;Illman et al, 2009;Berg and Illman, 2011b;Brauchler et al, 2011;Huang et al, 2011]. All these studies have consistently shown that transient HT can identify not only the pattern of the heterogeneous hydraulic conductivity field but also the variation of specific storage.…”
Section: Introductionmentioning
confidence: 99%